Russia’s Aggression against Ukraine and South Asia: What Are the Implications of Moscow’s Nuclear Blackmail for India and Pakistan? - Nitza-Makowska, Agnieszka (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2024)
This paper aims to examine the implications of Russia’s nuclear blackmail for India and Pa kistan, two nuclear-armed states that remain outside the UN Treaty on the Non-Proliferation of Nuclear Weapons framework and that have been engaged in a protracted conflict for over seven decades. Indeed, the trajectory of India and Pakistan’s rocky bilateral relationship in addition to Pakistan’s characterisation as a “terror state” lacking a “no-first-use” pledge in its nuclear doctrine has earned South Asia a reputation as a nuclear flash point. Therefore, considering the region’s fragile geopolitical and security situation, it is essential to identify whether and how India and Pakistan have reacted to the nuclear element of the war in Ukraine and what lessons these states can learn for their identities and behaviours as nuclear powers. To investigate that this paper triangulates selected primary and secondary sources on Putin’s nuclear signalling and its global implications, as well as New Delhi’s and Islamabad’s reactions to this performance. Both South Asian states adopted the so-called “neutral” standing vis-à-vis the war in Ukraine and distanced themselves from Putin’s nuclear signalling. The post-invasion period has wit nessed New Delhi and Islamabad emphasising the deterrent potential of their nuclear arsenals and avoiding nuclear rhetoric against each other. Celem artykułu jest zbadanie implikacji rosyjskiego szantażu nuklearnego dla Indii i Pakistanu – dwóch państw posiadających broń nuklearną, które pozostają poza układem o nierozprzestrzenianiu broni jądrowej, oraz są wzajemnie skonfliktowane od ponad siedmiu dekad. Dynamiczna trajektoria relacji indyjsko-pakistańskich, a także charakterystyka Pakistanu jako „państwa terrorystycznego” pozbawionego w swojej doktrynie nuklearnej zobowiązania „nie pierwszego użycia”, zapewniła Azji Południowej reputację nuklearnego punktu zapłonu. Dlatego też, biorąc pod uwagę niestabilną sytuację geopolityczną i bezpieczeństwa w regionie, istotne jest ustalenie, czy i w jaki sposób Indie i Pakistan zareagowały na nuklearny element wojny w Ukrainie oraz jakie wnioski te państwa mogą wyciągnąć dla swoich tożsamości mocarstw nuklearnych oraz związanych z tymi tożsamościami działań wobec siebie i poza Azją Południową. Aby przeanalizować te problemy, w artykule dokonano triangulacji wybranych źródeł pierwotnych i wtórnych dotyczących sygnalizacji nuklearnej Putina z naciskiem na jej globalne implikacje, oraz reakcji Nowego Delhi i Islamabadu na te działania. Indie i Pakistan przyjęły tzw. „neutralne” stanowisko wobec wojny w Ukrainie oraz zdystansowały się od nuklearnych sygnałów Putina. W okresie od rozpoczęcia inwazji New Delhi i Islamabad podkreślały odstraszający potencjał swoich arsenałów nuklearnych oraz unikały stosowania retoryki nuklearnej przeciwko sobie.
Agresja Rosji na Ukrainę a Azja Południowa: jakie są implikacje nuklearnego szantażu Moskwy dla Indii i Pakistanu?
Keywords: India; Pakistan; Russia; nuclear weapons; war in Ukraine; Indie; Rosja; broń nuklearna; wojna w Ukrainie